José Martí: historia de una bofetada - Antonio José Ponte (Nuevo mundo - Mundos Nuevos, 2008)
Does a functional Martí remain for Cuban politics? Haven’t the actual Cuban regime and the exiles exhausted his potentiality? I wonder if, from now on, we will not have to cast aside the mania that considers José Martí to be an irreproachable authority. I wonder if we will not have to dispense with, among other authoritarianisms, the Martí authoritarianism.